Pengaruh Air Rebusan Biji Alpukat Dan Daun Pandan Terhadap Kadar Gula Darah Penderita DM Tipe II Di Puskesmas Panarung Dan Bukit Hindu - Retno Ayu Hapsari; Yetti Wira Citerawati SY; Gabriella Marisa Konoralma (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2018)
An appropriate therapy is required in maintaining blood sugar levels (BSL) of type II DM. There are four pillars of diabetes management include education, diet, exercise and pharmacology. The aim of the study is to investigate the effect of avocado seeds and pandan leaves tea on BSL in type II DM at Community Health Center of Panarung and Bukit Hindu. This study was a one group pretest-posttest experimental design included 20 participants who were able participating in taking avocado seeds and pandan leaves tea. The result showed that at baseline, mean all participants’ BSL was 270.1±51.2 mg/dl. Mean BSL after consuming the tea was 245±51.2 mg/dl. The paired t-test revealed there was significant result (p<0.05) of consuming avocado seed and pandan leaves tea on decreasing BSL in type II DM. In conclusion, avocado seeds and pandan leaves tea indicating a profitable effect on reducing BSL in type II DM. However, a larger study is needed to determine the effect of avocado seeds and pandan leaves tea in vary people with type II DM.